The Influence Of Machinery Maintenance And Raw Material Supply On The Smoothness Of The Production Process (Survey at PT. Pacific Eastern Coconut Utma Pangandaran Factory) - Iqbal Nugraha; Suci Putri Lestari; Barin Barlian (Journal of Indonesian Management, 2023)
This study aims to determine the effect of Machine Maintenance and Raw Material Inventory on the smoothness of the Production Process (Survey at PT. Pacific Eastern Coconut Utama Pangandaran Factory). The method used in this study is a descriptive research method with a quantitative approach. The samples used are machine maintenance cost data, raw material inventory costs, and production cost data for the last 3 years, namely in the 2019-2021 period at PT. Pacific Eastern Coconut Utama. The analytical tool used in this study was multiple linear regression using SPSS Version 25. The results showed that simultaneous machine maintenance and raw material inventory had a significant effect on the smooth running of the production process with an Fcount of 32.134 and a probability significance value of 0.000<0.05. Partially, machine maintenance has no significant effect on the smooth running of the production process because the significance value of 0.084 is greater than 0.05. Partially raw material inventory has a significant effect on the smooth running of the production process with a significance value of 0.000 <0.05.